Fish Composition of Kwanar Farakwai Reservoir Igabi, Kaduna State, Nigeria - M, Tanko M.; M, Obioha (Darul Yasin Al Sys, 2024)
The research titled ‘Determination of Physico-Chemical Characteristics and Fish Composition of Kwanar Farakwai Reservoir Igabi, kaduna State, Nigeria’was conducted between July 2019 to June 2020. Reservoirs are natural or artificial lakes that provide habitat and food for many species of fish and wildlife. They are of significant importance because they hold populations of diverse fish species. A total of 942 fish comprising fourteen species belonging to 7 families were caught using an experimental gill net. Oreochromis niloticus dominated the catches with 405(43%) followed by Clarias gariepinus with 221 (23.46%). Monthly abundance of all the fish species caught, showed the highest in the month of October with 206 (21.87%), While January recorded 159 (16.88%) and the lowest was in June, 20 (2.12%). Fourteen species of fish belonging to Seven families with Cichlidae (53.5%) and Clariidae (39.7%) as the dominant families in both number and weight in the reservoir were recorded.